(untitled) (Research, Society and Development, 2022)
Photodynamic therapy using low-intensity laser has been used in implant dentistry as a complementary approach in the decontamination of the region, stimulating bone repair and exerting a bactericidal effect. In this context, the aim of the present study is to assess the importance of using laser therapy in the non-surgical treatment of peri-implant lesions. This is a literature review article, developed through a literature review in the Pubmed/Medline and Scielo databases. Studies published between 2006 and 2020, which showed availability of the full text and clarity in the methodological details used, were selected. According to the consulted literature, it can be concluded that the control of bacterial plaque is one of the main etiological factors of peri-implant diseases and that the treatment of peri-implantitis should be done according to the stage at which the disease presents. The use of low-intensity laser therapy is considered an additive to the treatment of peri-implantitis because it causes a bactericidal effect on aerobic and anaerobic microorganisms after surgical debridement.